Moving Image Theory : Ecological Considerations - Anderson, Barbara Fisher, 1951-; Anderson, Joseph, 1940- (Book collections on Project MUSE., 2007)
Blending unconventional film theory with nontraditional psychology to provide a radically different set of critical methods and propositions about cinema, Moving Image Theory: Ecological Considerations looks at film through its communication properties rather than its social or political implications. Drawing on the tenets of James J. Gibson's ecological theory of visual perception, the fifteen essays and forty-one illustrations gathered here by editors Joseph D. Anderson and Barbara Fisher Anderson offer a new understanding of how moving images are seen and understood.<B.